Conception of society and its characteristics from an Islamic perspective - Laluddin, Hayatullah (International Society of Muslim Philosophers and Theologians (ISOMPT)andDepartment of Theology and Philosophy, National University of Malaysia., 2014)
Islam presents a unique and comprehensive view of the concept of society. For, it perceives it as an association formed in accordance with the Divine revelation contained in Quran and the Sunnah of the prophet, synthesising material, and the spiritual aspects of human life. It views society as an organic whole, where all aspects of life are considered as a component part of the body hence, negating sectarianism and racism. Therefore, this paper attempts to illuminate the concept of society from Islamic perspective and analyse the nature and characteristics of social order in Islam. It also throw some light on the social principles devised by Islam for the formation of an integrated social system, and the measures for nourishment and nurturing of the internal and external aspects of human nature. Using an analytical approach the paper concludes that Islam presents a dynamic conception of the society embodying universal characteristics hence, capable of transforming all humanity to a single brotherhood.